2017
DOI: 10.1002/pmic.201700018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between chaotropic and detergent‐based sample preparation workflow in tendon for mass spectrometry analysis

Abstract: Exploring the tendon proteome is a challenging but important task for understanding the mechanisms of physiological/pathological processes during ageing and disease and for the development of new treatments. Several extraction methods have been utilised for tendon mass spectrometry, however different extraction methods have not been simultaneously compared. In the present study we compared protein extraction in tendon with two chaotropic agents, guanidine hydrochloride (GnHCl) and urea, a detergent, RapiGest™,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…The measured rate constants of protein turnover will also be dependent on the protein extraction methods used. We chose GuHCl extraction for whole tendon as this has previously been shown to result in best proteome coverage for tendon (Ashraf Kharaz et al, 2017). It was not possible to use the same extraction method for laser-captured samples due to the small amount of starting material, therefore we used a method previously optimised for this sample type (Thorpe et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured rate constants of protein turnover will also be dependent on the protein extraction methods used. We chose GuHCl extraction for whole tendon as this has previously been shown to result in best proteome coverage for tendon (Ashraf Kharaz et al, 2017). It was not possible to use the same extraction method for laser-captured samples due to the small amount of starting material, therefore we used a method previously optimised for this sample type (Thorpe et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Tendons were finely chopped, flash frozen in liquid nitrogen and pulverised in a dismembrator (Sartorius, mikro-dismembrator U, 1800rpm, 2 mins.). Proteins were extracted using previously optimised methodologies (Ashraf Kharaz et al, 2017). Briefly, following deglycosylation in chondroitinase ABC, proteins were extracted in guanidine hydrocholoride (GuHCl) as described previously (Kharaz et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This could reflect differences in extractability of previously synthesised heterotrimeric and homotrimeric collagen (I) molecules due to altered crosslinking (Pfeiffer et al, 2005). In this study, we used an extraction method for the insoluble pellet previously shown to increase the identification of collagenous proteins (Ashraf Kharaz et al, 2017) However, it may be that pepsinisation of the insoluble pellet (Peffers et al, 2014) to break mature crosslinks between telopeptides would have released more homotrimeric collagen (I), and hence alpha-1(I) chain (COL1A1) peptides from Dupuytren's tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Combined flow-throughs were acidified with Trifluoroacetic acid to 0.2% (v/v). Incubation media was bound to and digested off Strataclean beads as previously described (Angi et al, 2016;Ashraf Kharaz et al, 2017). A yeast enolase peptide standard was added to each sample, though this was not utilised for later quantification.…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…Proteomics. Proteomics was performed as reported in previous studies (3,27,40) Raw spectra were converted to mgf files using Proteome Discovery (Thermo Scientific, Loughborough, UK) and resulting files were searched against the UniProt mouse sequence database using a Mascot server (Matrix Science, London, UK). Search parameters used were: peptide mass tolerance, 10ppm; fragment mass tolerance, 0.01Da; +1,+2,+3 ions; missed cleavages 1; instrument type ESI-TRAP.…”
Section: Methodsmentioning
confidence: 99%